Previous miscarriage and the subsequent risk of preterm birth in Scotland, 1980–2008: a historical cohort study. (28th January 2015) - Oliver‐Williams, C; Fleming, M; Wood, AM; Smith, GCS
<x xml:space="preserve">Abstract</x> Objective To determine whether the relationship between previous miscarriage and risk of preterm birth changed over the period 1980–2008, and to determine whether the pattern varied according to the cause of the preterm birth. Design Linked birth databases. Setting All Scottish NHS hospitals. Population A total of 732 719 nulliparous women with a first live birth between 1980 and 2008. Methods Risk was estimated using logistic regression. Main outcome measures Preterm birth, subdivided by cause (spontaneous, induced with a diagnosis of pre‐eclampsia, or induced without a diagnosis of pre‐eclampsia) and severity [extreme (24–28 weeks of gestation), moderate (29–32 weeks of gestation), and mild (33–36 weeks of gestation)]. Results Consistent with previous studies, previous miscarriage was associated with an increased risk of all‐cause preterm birth (adjusted odds ratio, aOR 1.26; 95% confidence interval, 95% CI 1.22–1.29). This arose from associations with all subtypes. The strongest association was found with extreme preterm birth (aOR 1.73; 95% CI 1.57–1.90). Risk increased with the number of miscarriages. Women with three or more miscarriages had the greatest risk of all‐cause preterm birth (aOR 2.14; 95% CI 1.93–2.38), and the strongest association was with extreme preterm birth (aOR 3.87; 95% CI 2.85–5.26). The strength of the association between miscarriage and preterm birth decreased from 1980 to 2008. This was because of weakening associations with spontaneous preterm birth and induced preterm birth without a diagnosis of pre‐eclampsia. Conclusions The association between a prior history of miscarriage and the risk of preterm birth declined in Scotland over the period 1980–2008. We speculate that changes in the methods of managing incomplete termination of pregnancy might explain the trend, through reduced cervical damage.